KONSEP TA’DIB MENURUT AL-ATTAS DAN KAITANNYA DENGAN DEWESTERNISASI DAN ISLAMISASI ILMU - Husni, Rahmatul (FIKRAH, 2023)
Al-Attas revealed that the challenge of this century is the degradation of knowledge so that humans can no longer distinguish between truth and falsehood (the loss of civilization). The science that is falsified or used as tools and materials of indoctrination for the benefit of personal passions, is precisely by the scientists themselves. The core issue lies not in the illiteracy or ignorance of the general population but rather in the misinterpretation of science or the disorder in scientific understanding resulting from the emulation of the Western perspective, which significantly differs from the Islamic worldview. This research analyzes the educational concept of Syed Naquib Al-Attas. As a result, there are three magnificent concepts from al-Attas's thought which subsequently known as the concept of Islamization of science, i.e: semantic analysis – linguistics which is used as a strong argument to support opinions, mastery of Islamic and Western treasures, and wisdom in seeing the ulama and Islam of the Malays.